Evidence of fire-sale M&A in European transition countries - Višić, Josipa (Managing global transitions, 2012)
The aim of this paper is to determine differences in variables that create investment climate and therefore affect the values of incoming crossborder M&A in selected European transition countries. Cluster analysis for 1999 and 2007 shows that countries with unfavourable investment climate received high levels of incoming cross-border M&A. Sole country in the cluster characterised by healthy investment area (Slovenia) had the highest gdp per capita accompanied with the lowest values of incoming cross-border M&A relative to its GDP. These results could be interpreted as an evidence of fire-sale M&A in most European transition countries. In 2010, situation changed and although recession left trace, data on cross-border M&A indicate that foreign investors focused more on companies which operated in countries with healthier economy. These results indicate that a healthy investment climate is necessary to provide a sustainable economic development of a country.
Keywords: cross-border M and A; mednarodne združitve in pripojitve; tržna cena; fire-sale M and A; sustainable economic development; trajnostni gospodarski razvoj; investicijsko okolje; investment climate